Beneficio económico de la implementación del suministro de material médico por el sistema de dosis unitaria en dos servicios del hospital nacional edgardo rebagliati martins” - Ortega Cueva, Lila Paola (2010)
The technical standard of health Drug Dispensing System Single-Dose (DDSSD) is to promote access and the safe and rational use of medicines and surgical medical equipment in hospitals, through the proper implementation and DDSSD strengthening of the Departments and Pharmacy Services health sector establishments. This is a descriptive study of relevant information that reflects the economic benefit represented the implementation of the provision of medical supplies through the services DDSSD Rheumatology, Endocrinology and Dermatology (4A) and General Surgery (4B) Hospital Nacional Edgardo Rebagliati Martins (HNERM) during the first year of implementation. Objective: To determine the economic benefit that represented the implementation of the provision of medical supplies by the DDSSD HNERM two services during the period 15 August 2008 - August 31, 2009 for the period August 1, 2007 - 14 August 2008. Results: a) the recovery of daily returns of medical supplies during the period August 1, 2007 - 14 August 08 and August 15, 1908 - August 31, 2009, giving a result of S /. 15759.40 for the second period in favor of Pharmacy, Medical Equipment, the period before the start of the implementation of DDSSD of medical equipment did not generate any return for the institution, b) The measurement of medical supplies requested the Medical Supplies Depot HNERM by 4A and 4B services amounted to S /. 111,681.12 for the period August 1, 2007 - August 14, 08 and requested medical equipment Pharmacy Medical Equipment for the same services S /. 96754.15 for the period August 15, 2008 - August 31 09. The saving of medical equipment distributed through DDSSD compared to the traditional distribution prior to S /. 14926.97 for the new system implemented. Conclusion: The percentage difference between the traditional system of distributing medical supplies in the HNERM and the new distribution by DDSSD was 13.37% in favor of the institution in its first year.